2023
DOI: 10.1155/2023/9929835
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Periodontitis in Patients with and without HIV

Abstract: Purpose. The aim of this study was to compare clinical periodontal conditions in HIV-positive people on HAART with an HIV-negative group, in addition to investigating factors associated with periodontitis in the entire sample. Methods. This was a cross-sectional study. Data were collected by oral clinical examination for the diagnosis of periodontitis, review of medical records, and application of a questionnaire containing personal data, deleterious habits, and oral hygiene habits for the other variables. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…[ 36 , 37 ] In a recent review, it has been suggested that the characteristics of biological aging-cellular senescence, stem cell exhausation and immunoaging are also involved in maintaining periodontal homeostasis leading to increased tooth loss in subjects whose biological age at baseline is higher than their chronological age. [ 38 ] Other studies have shown that as people with HIV get older they are more likely to develop moderate to severe periodontal disease [ 39 ] and have increased tooth loss. [ 40 ] Therefore in order to maintain a functional dentition (> 20 teeth present) in peole with HIV throughout their lifetime, it is important to aggressively treat periodontal disease earlier to prevent future tooth loss as they potentially undergo accelerated biological cellular aging in the periodontal complex.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 , 37 ] In a recent review, it has been suggested that the characteristics of biological aging-cellular senescence, stem cell exhausation and immunoaging are also involved in maintaining periodontal homeostasis leading to increased tooth loss in subjects whose biological age at baseline is higher than their chronological age. [ 38 ] Other studies have shown that as people with HIV get older they are more likely to develop moderate to severe periodontal disease [ 39 ] and have increased tooth loss. [ 40 ] Therefore in order to maintain a functional dentition (> 20 teeth present) in peole with HIV throughout their lifetime, it is important to aggressively treat periodontal disease earlier to prevent future tooth loss as they potentially undergo accelerated biological cellular aging in the periodontal complex.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, HIV has been reported to contribute to the deterioration of oral health, which is considered an early clinical manifestation of HIV infection 67 . A recent cross‐sectional study observed that HIV might be positively related to periodontitis, potentially attributed to the side effects of medications, 68 However, some study reveals a negative correlation. One possible explanation lies in the alterations to the microbiomes in HIV patients.…”
Section: Discussionmentioning
confidence: 99%